Sequence analysis of the VP7 gene of human rotavirus G1 isolated in Japan, China, Thailand, and Vietnam in the context of changing distribution of rotavirus G-types - Duy Trinh Quang (2018)
Over the last decade, rotavirus G1 has represented the most common genotype worldwide. Since 2000, the prevalence of rotavirus G1 has decreased in some countries such as Japan and China. To monitor the trend of the VP7 encoding gene of rotavirus G1, we performed a sequence analysis of 74 G1 rotavirus strains isolated in Japan, China, Thailand, and Vietnam during the period from 2002 to 2005. The phylogenetic tree showed that all of the studied G1 strains from the four countries clustered into lineage III, the same as the majority of the G1 strains isolated in China and Japan in 1990 and 1991. Examination of the deduced amino acid sequences of the G1 strains from China and Japan revealed an amino acid substitution at position 91 (Asn instead of Thr) in antigenic region A when compared to the G1 strains isolated in China and Japan in 1990, 1991, and global reference strains. For the G1 strains from Thailand and Vietnam, there were three amino acid substitutions, not belonging to any antigenic regions. The study showed that there have been no considerable changes of human rotavirus G1 isolated in Japan, China, Thailand, and Vietnam. Further studies need to be carried out for a better understanding of why such changes in the prevalence of rotavirus G1 occur in these countries. © 2007 Wiley-Liss, Inc.